COVID-19 Pandemic-Related Restrictions: Factors That May Affect Perinatal Maternal Mental Health and Implications for Infant Development - Kokkinaki, Theano; Hatzidaki, Eleftheria (Frontiers in Pediatrics, 2022)
This review aims to discuss the factors that may affect maternal mental health and infant development in Covid-19 pandemic condition. Towards this direction, the two objectives of this review are the following: a) to discuss possible factors that may have affected negatively perinatal mental health through the pandemic-related restrictions; and b) to present the implications of adversely affected maternal emotional wellbeing on infant development. We conclude that the pandemic may has affected maternal mental health with possible detrimental effects for the infants of the Covid-19 generation. We highlight the need for evidence-based interventions to be integrated within the health system for prenatal and postpartum care in an effort to promote maternal mental health and infant development.